Narratives of occupational therapy students from the Philippines on virtual internship - Comia, Gwyneth; Manalo, Jan Ericka; Areglado, Hanna Patricia; Rivera, Zaira Claudine; Delos Reyes, Rod Charlie (The Journal of Practice Teaching and Learning, 2023)
Virtual internships became an alternative work-based learning for the continuity of education affected by the pandemic. This transition made an impact on the internship experience of Filipino students, particularly the occupational therapy students in delivering services. Occupational therapy (OT) is a client-centered profession that focuses on the therapeutic use of activities in treating impairments that hinder an individual’s occupational participation. This study aims to explore experiences of OT interns from CALABARZON, a region in the Philippines during virtual internships. A phenomenological study approach was utilized. Six (6) OT interns from different universities in CALABARZON participated in a focus group discussion via ZOOM video conferencing platform. Data collected were recorded, transcribed, and analyzed through thematic analysis. Five themes emerged: (1) preparation to virtual internship through bridging programs; (2) positive experiences, attitudes, and practices in virtual internship; (3) perceived advantages and disadvantages of virtual internship; (4) challenges and additional demands in virtual internship; and (5) preview of real occupational therapy through virtual internship.